PENETAPAN KADAR ASAM LEMAK BEBAS PADA SABUN MANDI CAIR MEREK “LX” DENGAN METODE TITRASI ASIDIMETRI - ROSMIDAH SIMANJUNTAK (LP2MTBM MAKARIOZ, 2018)
Along with the increase in the community's need for bath soap, the number of products and types of bath soap on the market is always increasing. Various bath soap industries are competing to promote the superiority of their respective products so that they sometimes look so excessive and can mislead consumers. In determining the levels of free fatty acids carried out by the method of acidimetry titration. The free fatty acid levels obtained in this experiment were 4.75%.